Peculiarities of Maturity of the Relationships of Senior Pupils with the World - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2000)
In this article, personal relationships with the world are regarded as the foundation for the dispersion of spirituality. Spirituality is understood here as a complex integral feature which reveals itself through a diverse and permanent connection of a person with the world. The most important types of relationships through which spirituality reveals itself include first of all relationships of an individual with other people and with himself/herself at the same time as well as with social communities. Therefore the article analyses the peculiarities of relationships of X-XI form pupils with their parents, friends, teachers and their own selves. Furthermore, the article touches upon the relationships of the pupils of this age group with their nation state and church. Similarities and contrasts of the development of the said relationships are revealed on the basis of empirical material.